2022
DOI: 10.1139/cjz-2021-0167
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomy and ultrastructure of kidney interstitial cells and nephron in brown trout (Salmo trutta) at different stages of the life cycle

Abstract: The study focuses on the microanatomy and ultrastructural changes in the trunk kidney interstitium cells and nephrons in parr, smolt and spawning brown trout Salmo trutta Linnaeus, 1758 sampled in Luga River and Solka River, the tributaries of the Baltic Sea. Regardless of the type of cells or their structure, there were changes in their areas and the number and structure of organelles responsible for the transport, synthetic and energetic function of cells. Our data on the morphology of the nephron combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Several organs are involved in osmoregulation: the kidneys, gills, digestive tract, bladder, and endocrine glands [4]. Previous studies on Pseudetroplus maculatus (Bloch 1795), Alburnus escherichii Steindachner 1897, and Salmo trutta showed that adaptation to a hyperosmotic environment leads to a decrease in the diameter of Bowman's capsules, accompanied by a decrease in glomerular filtration rate, which indirectly indicates a reduction in the formation of primary urine [10,20,21]. Moreover, smolts can have epithelial cells that are smaller in area and height in their proximal tubules, which indicates a low glomerular filtration rate, a distinctive characteristic of marine fishes [8,9,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several organs are involved in osmoregulation: the kidneys, gills, digestive tract, bladder, and endocrine glands [4]. Previous studies on Pseudetroplus maculatus (Bloch 1795), Alburnus escherichii Steindachner 1897, and Salmo trutta showed that adaptation to a hyperosmotic environment leads to a decrease in the diameter of Bowman's capsules, accompanied by a decrease in glomerular filtration rate, which indirectly indicates a reduction in the formation of primary urine [10,20,21]. Moreover, smolts can have epithelial cells that are smaller in area and height in their proximal tubules, which indicates a low glomerular filtration rate, a distinctive characteristic of marine fishes [8,9,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…; endocytosis zone and a portion of the brush border in an adult S from the Barents Sea population (g). Cell units: urinary space (1), basement membrane (2), squamous epithelial cell (3), podocytes (4), cytopodia (5), endothelial cell (6), fenestra endothelial cells (7), capillary (8), nucleus (9), mitochondria (10), rough endoplasmic reticulum (11), gap junction (12), smooth endoplasmic reticulum (13), tubular endoplasmic reticulum (14), microfibrils (15), brush border microvilli (16), vesicle (17), secretory granules (18). The parietal layer of Bowman's capsule is formed by a basement membrane lined with squamous epithelial cells with centrally located nuclei.…”
Section: Trunk-kidney Ultrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the outer diameter of the tubules depends both on the lumen of the tubules and on the height of the epitheliocytes that form the tubules. The height of nephron epithelial cells increases in the following order: P. senegalus —freshwater bony fish— C. punctatus , Coregonus migratorius—lungfish P. dolloi —amphibian Bufo bufo [ 15 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%